Status and Future Outlook of Cultivated Mushroom Sector in Turkey - Erkan Eren; Aysun Pekşen (Turkish Journal of Agriculture: Food Science and Technology)
Mushroom production that started in 1960's in Turkey gained economic value from the 1990's and it started improving as a commercial sector after that time. While Turkey mushroom production was 80 tons in 1973, it increased up to 45.000 tons in 2014. There is a rapid changes and improvement in cultivated mushroom production and consumption in Turkey. The object of the study is to reveal current status of mushroom production in the world and Turkey, and the problems of the mushroom sector in Turkey and the necessary precautions and ways to solve these problems. The data obtained from the inspections of the mushroom enterprises that in mushroom production regions of Turkey, and the secondary data obtained from Food and Agriculture Organization of the United Nations (FAO), Turkish Statistical Institute (TUIK) and Union of Antalya Exporters (AIB) and also national and international publication’ data has been used in this study. In Turkey, Mediterranean and Marmara Regions rank first in mushroom production and consumption with the share of 61.5 and 40%, respectively. It has been determined that big enterprises producing mushroom and compost established in the Central Anatolia in this study. The number of enterprises producing mushroom by using technology increases and 15-20% of the total production are provided by the big enterprises having 2000 m2 and over mushroom production areas. Recent years, there are serious increases in the production of different mushroom species such as especially Pleurotus ostreatus. In addition, precision agriculture applications are widespread with the time. For the continuation of growth of the mushroom sector in Turkey and the solving of the sector problems, there are needs both in making the necessary changes in legislation and to be given priority researches related to mushroom production in university and public research institutions and also to support them.